Functional Outcomes of Insertional Achilles Tendinopathy Treatment: A Systematic Review. Issue 6 (June 2021) - Jarin, Ian J.; Bäcker, Henrik C.; Vosseller, J. Turner
Abstract : Background: Achilles tendinopathy is a common clinical problem that can be either insertional or noninsertional, and effective treatment of each type can vary. We sought to investigate the current evidence on different treatment methods for insertional Achilles tendinopathy with a focus on functional outcomes. Methods: We performed a systematic review of the available literature using the PubMed/MEDLINE and Cochrane Central Register of Controlled Trials databases. Data from included studies were categorized according to treatment method and reported with respect to functional outcomes and complications. Results: A total of 1, 457 abstracts were reviewed; 54 studies with 2, 177 patients met the inclusion criteria. Among the 54 studies, 6 operative techniques and 6 nonoperative treatments were evaluated. Conclusions: Eccentric exercises and low-energy extracorporeal shockwave therapy (ESWT) have the greatest evidence for the initial management of insertional Achilles tendinopathy. ESWT has been increasingly studied in recent years, but more high-quality evidence is needed. Operative treatment with tenotomy, debridement, retrocalcaneal bursectomy, and calcaneal exostectomy is effective. Flexor hallucis longus tendon transfer may benefit cases of more severe disease. Minimally invasive procedures have a potential role in the treatment algorithm and require more rigorous study. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.